85.6k views
7 votes
6a-4(2a+3)

what is the answer

HELP Thank you

2 Answers

10 votes

Answer:


\Longrightarrow: \boxed{\sf{-2a-12}}

Explanation:

Use the distributive property.


\underline{\text{DISTRIBUTIVE PROPERTY:}}\\\\\Longrightarrow: \sf{A(B+C)=AB+AC}

6a-4(2a+3)

First, multiply by expand.

⇒ -4(2a+3)

⇒ -4*2a=-8a

⇒ -4*3=-12

⇒ -8a-12

→ 6a-8a-12

Solve.

Add or subtract the numbers from left to right.

⇒ 6a-8a=-2a

= -2a-12


\Longrightarrow: \boxed{\sf{-2a-12}}

  • Therefore, the correct answer is -2a-12.

I hope this helps! Let me know if you have any questions.

User Rachie
by
4.9k points
8 votes

Answer:


\huge\boxed{\bf\:2 (-a - 6)}

Explanation:


6a - 4(2a + 3)\\6a - (4*2a + 4*3)\\6a - (8a + 12)\\6a - 8a - 12\\- 2a - 12\\\boxed{\bf\:2 (-a - 6)}

Steps:

  • Factorise the second term as the first is already in its simplified form.
  • Solve the first term and the second term by doing the required arithmetic operations.
  • Take the common factor out.
  • The result will be : 2 (- a - 6).


\rule{150pt}{2pt}

User MrN
by
5.2k points